LEGAL CONSEQUENCES FOR DEVELOPERS WHO MAKE GAMES CONTAINING ADULT CONTENT IN INDONESIA - Rama, Bagus Gede Ari (Kerta Dyatmika, 2024)
This study examines the legal framework governing adult content in video games in Indonesia, with particular reference to the Electronic Information and Transactions Law (Law No. 11 of 2008) and Ministerial Regulation No. 11 of 2016. Employing a normative legal research method, the study investigates how these legal instruments aim to protect minors through age-based content classifications and other regulatory mechanisms. The analysis applies statutory, responsive, utilitarian, and natural law theories to assess the effectiveness of the current legal provisions. The findings indicate that video game developers may be subject to administrative, criminal, and civil sanctions if their games contain adult content that contravenes legal standards. The study concludes that legal regulations must be adaptive to technological developments and regional particularities in order to ensure the effective protection of minors from exposure to inappropriate content.